De Europa y América : (1955-1960) / Gabriel García Márquez ; recopilación y prólogo de Jacques Gilard - Gilard, Jacques; García Márquez, Gabriel (Narradores de hoy; 76)
Es el vol. 4 de "Obra periodística"